2015
DOI: 10.1111/joa.12376
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of the inner ear

Abstract: The identification of transcriptional differences has served as an important starting point in understanding the molecular mechanisms behind biological processes and systems. The developmental biology of the inner ear, the biology of hearing and of course the pathology of deafness are all processes that warrant a molecular description if we are to improve human health. To this end, technological innovation has meant that larger scale analysis of gene transcription has been possible for a number of years now, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 120 publications
(182 reference statements)
0
11
0
Order By: Relevance
“…The first transcriptome profiling experiment on cochlear tissue was performed Cho et al (2002) . Since then, a large number of studies have leveraged microarray, PCR, and RNA sequencing (RNA-seq) technologies to explore the auditory transcriptome ( Schimmang and Maconochie, 2016 ). Low-input reverse transcription and RNA isolation technologies have revolutionized these studies, facilitating cell type-specific transcriptomics.…”
Section: Introductionmentioning
confidence: 99%
“…The first transcriptome profiling experiment on cochlear tissue was performed Cho et al (2002) . Since then, a large number of studies have leveraged microarray, PCR, and RNA sequencing (RNA-seq) technologies to explore the auditory transcriptome ( Schimmang and Maconochie, 2016 ). Low-input reverse transcription and RNA isolation technologies have revolutionized these studies, facilitating cell type-specific transcriptomics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by using gene arrays, fewer genes were reported to be expressed differently in the adult rat cochlea suffered from noise treatment 42,43 , but more genes were found to be expressed differentially in the mouse cochlear sensory epithelia in postnatal day-3, compared to those at adult 17 . In general, the RNA presence and quantity can be indicated from a whole genome in time using RNA-seq, whereas cDNA microarrays only identify the limited allele variants designed into the microarrays 20,44 . Thus, this study provides a relatively more complete candidate genes or pathways which play roles in hair cell regeneration in the mouse cochlea, particularly from the comparative perspective with chick hair cell regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In general, most genes and signaling pathways which have been shown to be involved in the embryonic development of hair cells are also required for hair cell regeneration 6,7 . Given the advantages of high-throughput sequencing, cDNA microarrays, SAGE or RNA-seq have been used to investigate a global gene expression during hair cell regeneration in rats or mice 1720 and nonmammals 19,2126 . Our recent study found that about 800 genes were differentially expressed during chick hair cell regeneration, some of which were grouped into approximately one hundred signaling pathways, including Notch, Wnt, Fgf and Bmp.…”
Section: Introductionmentioning
confidence: 99%
“…Auditory phenotypic diversity might be related to changes in gene expression. Significant efforts have been made to profile gene expression patterns in mouse inner ears at different developmental stages, as well as following various stimuli, physiological damage, and specific gene knock out [ 24 , 25 , 26 , 27 ]. Dong et al (2013) reported that inner ear gene expression differs between echolocating bats and non-echolocating bats via a transcriptome analysis and identified several candidate genes related to echolocation ability [ 28 ].…”
Section: Introductionmentioning
confidence: 99%